2012
DOI: 10.1007/s00406-012-0377-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine on social cognition, social competence and self-reported stress in schizophrenia patients and healthy controls

Abstract: More than 80 % of patients diagnosed with schizophrenia are nicotine-dependent. Self-medication of cognitive deficits and an increased vulnerability to stress are discussed as promoting factors for the development of nicotine dependence. However, the effects of nicotine on social cognition and subjective stress responses in schizophrenia are largely unexplored. A 2 × 2-factorial design (drug × group) was used to investigate the effects of nicotine versus placebo in smoking schizophrenia patients and healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…In contrast, a recent study involving a human laboratory model of psychosis did not find nicotine to be different from placebo when assessing both positive and negative symptoms and cognitive effects (D'Souza et al, 2012). Other work has found nicotine to be similarly ineffective in improving social cognition and subjective stress responses (Drusch et al, 2013). …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, a recent study involving a human laboratory model of psychosis did not find nicotine to be different from placebo when assessing both positive and negative symptoms and cognitive effects (D'Souza et al, 2012). Other work has found nicotine to be similarly ineffective in improving social cognition and subjective stress responses (Drusch et al, 2013). …”
Section: Introductionmentioning
confidence: 96%
“…Few clinical trials have been designed to explore nicotinic agents for the specific management of agitation, irritability, and aggression specifically; however, evidence supporting a significant but complex role of nicotine and nicotinic receptors in these syndromes can be gleaned from a variety of clinical studies with different primary outcomes that also report on these data (Arnold et al, 2012; Conners et al, 1996; Drusch et al, 2013; Newhouse et al, 1994), as well as well-conducted case series (Mayer et al, 2001; Rosin et al, 2001). A second line of evidence comes from a number of studies describing the prominence of ARBS in the context of nicotine withdrawal (Lucidarme et al, 2010), and the tendency for these symptoms to resolve following administration of nicotine (Schechter, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, one behavioral study observed improved social cognition after acute nicotine administration in nonsmoking schizophrenia patients (Quisenaerts et al, 2013). Another study, however, found no neuronal or behavioral effects of the drug during social cognition in the illness (Drusch et al, 2013). As this area remains understudied, additional research is needed to clarify the role of the MCC in social cognition deficits in schizophrenia as well as to examine the ability of nicotine and other drugs to target the associated circuitry.…”
Section: Discussionmentioning
confidence: 98%
“…Growing body of evidence showed that patients affected with schizophrenia demonstrate cognitive deficit [31, 32] and cholinergic abnormalities, such as reduced acetylcholine in different brain structures [33] as well as widespread decrease in the level of muscarinic receptors in the postmortem brain [3436]. Cholinergic involvement in schizophrenia is further supported by the fact that muscarinic antagonists can evoke a psychotic state (“antimuscarinic psychosis/syndrome”), which includes a range of cognitive and psychotic symptoms resembling schizophrenia [37].…”
Section: Discussionmentioning
confidence: 99%